If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -9) = 20(x + 4) Reorder the terms: 4(-9 + 3x) = 20(x + 4) (-9 * 4 + 3x * 4) = 20(x + 4) (-36 + 12x) = 20(x + 4) Reorder the terms: -36 + 12x = 20(4 + x) -36 + 12x = (4 * 20 + x * 20) -36 + 12x = (80 + 20x) Solving -36 + 12x = 80 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. -36 + 12x + -20x = 80 + 20x + -20x Combine like terms: 12x + -20x = -8x -36 + -8x = 80 + 20x + -20x Combine like terms: 20x + -20x = 0 -36 + -8x = 80 + 0 -36 + -8x = 80 Add '36' to each side of the equation. -36 + 36 + -8x = 80 + 36 Combine like terms: -36 + 36 = 0 0 + -8x = 80 + 36 -8x = 80 + 36 Combine like terms: 80 + 36 = 116 -8x = 116 Divide each side by '-8'. x = -14.5 Simplifying x = -14.5
| 7-0.3x=4 | | 24x-18-16x=4(2x-5)+2 | | 34-5x=15+4x | | 7(x+3)-8=4x+3(3+x) | | 4x+y=-1 | | 80-5x=13x+18 | | 1xy^2-2x+5xy^2= | | 5(3x-8)-4(x+1)-18x= | | -4p+5+5p=12 | | 4x-1x+140=40 | | 5x^2+3x=8x | | -21=-7z | | 11-9x=159-37x | | B=qn+q | | x^2=-3x+18 | | 3(x-3)-15=0 | | 4(6z+1)-7=189 | | 27x+12=3(7x+7)+6x-9 | | 11x-(2x-7)=79 | | -6-9= | | 25=-3(22-b)+2(b-2) | | 119-5x=5x+9 | | 5n+40=45 | | k^2+3k=108 | | x+9=5(4x+-2) | | 10x+10-9x=16 | | -8-6x=8-8x | | 3.1x=2.3x+4.8 | | 5x+4=3x-4 | | 5(x+6)+10=10x-5(x-5) | | 7-4(x+3)-5=7+2(4-2x)-16 | | 2c+6c+5c-6= |